Bathing Practices as a Religious and Medical Encounter: Water, Climate and Health Across Monsoon Asia - Bianchini, Francesco (Religions, 2025)
This study explores the intersection between religious and medical bathing practices across Monsoon Asia, with particularly reference to āyurvedic and Buddhist traditions. While previous scholarship has emphasised the ritualistic and social dimensions of bathing in Brahmanical and Buddhist contexts, this article complements it with discussions of its medicinal and healing functions, as outlined in classical texts and displayed in material culture. The research highlights how bathing was considered essential for maintaining bodily balance—a concept analogous to humoral theory in Galenic medicine—across different climatic and environmental conditions, particularly during the monsoon season. The article further examines the transregional circulation and localisation of these practices, considering how diverse Asian cultures adapted Indic bathing traditions to their unique climatic and cultural contexts. Notably, the study addresses the complex interplay between religious doctrines, health and environmental factors, drawing connections between āyurvedic principles and Buddhist medical discourses. The findings suggest that while the notion of balance in bathing practices was widespread, its interpretation and implementation varied significantly across regions, reflecting local environmental and cultural influences. Through a comparative analysis of sources from South Asia, China and Southeast Asia, this article provides a nuanced understanding of how religio-medical bathing practices were shaped by and responded to the diverse climatic realities of Monsoon Asia.